PENGARUH KOMUNIKASI INTERPERSONAL, PENGETAHUAN TENTANG LINGKUNGAN DAN MOTIVASI PENINGKATAN PENDAPATAN TERHADAP PARTISIPASI DALAM PELESTARIAN LINGKUNGAN WISATA - H.D. Melva Meinaria Sitanggang (Program Studi Pendidikan Kependudukan dan Lingkungan Hidup, 2010)
The objective of this research is to know the effect of level interpersonal communication,enviromental knowledge and motivation increasing income which participation people in eternal a tour. Theresearch is done by using survey method to 80 respondents are inhabitants around Danau Toba from 2 (two)district; Simalungun and Samosir, North Sumatera.The results this research are : 1. There is direct effect of interpersonal communication to people’smotivation increasing income; 2. There is direct effect of enviromental knowledge to people’s motivationincreasing income; 3. There is direct effect of interpersonal communication to people’s participation ineternal a tour; 4. There is direct effect of environmental knowledge to people’s participation in eternal ator; 5. There is direct effect of people’s motivation increasing income to people’s participation in eternal atour.Results of this research give implication that people’s participation to eternal a tour is highlydetermined by interpersonal communication, environmental knowledge, and motivation increasing income.